Evaluating guselkumab: an anti-IL-23 antibody for the treatment of plaque psoriasis - Yang, Eric J (Drug Des Devel Ther, 2019)
The approval of guselkumab marks the entry of the IL-23 inhibitor class into the therapeutic armamentarium for patients with moderate-to-severe plaque psoriasis. This class specifically targets the upstream portion of the type 17 helper T (Th17) axis, which has been implicated as a key driver of the abnormal inflammatory state observed in psoriasis. Guselkumab is highly efficacious, with over 85% of the patients achieving ≥75% reduction in Psoriasis Area and Severity Index from baseline (PASI 75) and over 70% of the patients achieving PASI 90 response in its Phase III clinical trials. Additionally, this medication is well-tolerated, with non-serious infections such as nasopharyngitis and upper respiratory infections (URIs) being the most common adverse events (AEs) reported in its clinical trials. Guselkumab offers yet another effective treatment option in the rapidly growing list of available biological therapies for moderate-to-severe plaque psoriasis.